Math Problem Statement

DIRECTION

: Find the sum of the terms for each sequence below.

SEQUENCE

SOLUTION

nth term

  1. 1,4,7, 10...

  2. 3, 5, 7, 9, 11, ...

  3. 2, 4, 6, 8, 10, ....

4.-1, 1, -1, 1, -1, 1, ...

  1. 1, ½, 1/3, %, 1/5,...

Solution

Let's analyze each sequence and find the sum of the terms.

1. Sequence: 1, 4, 7, 10, ...

This is an arithmetic sequence with a common difference d=3d = 3.

General form: an=a1+(n1)d=1+(n1)3=3n2a_n = a_1 + (n-1) \cdot d = 1 + (n-1) \cdot 3 = 3n - 2

Sum of the first nn terms SnS_n for an arithmetic sequence is given by: Sn=n2(a1+an)S_n = \frac{n}{2} \cdot (a_1 + a_n)

Substitute a1=1a_1 = 1 and an=3n2a_n = 3n - 2:

Sn=n2(1+(3n2))=n2(3n1)=n(3n1)2S_n = \frac{n}{2} \cdot (1 + (3n - 2)) = \frac{n}{2} \cdot (3n - 1) = \frac{n(3n - 1)}{2}

2. Sequence: 3, 5, 7, 9, 11, ...

This is also an arithmetic sequence with a common difference d=2d = 2.

General form: an=3+(n1)2=2n+1a_n = 3 + (n-1) \cdot 2 = 2n + 1

Sum of the first nn terms: Sn=n2(a1+an)=n2(3+(2n+1))=n2(2n+4)=n(n+2)S_n = \frac{n}{2} \cdot (a_1 + a_n) = \frac{n}{2} \cdot (3 + (2n + 1)) = \frac{n}{2} \cdot (2n + 4) = n(n + 2)

3. Sequence: 2, 4, 6, 8, 10, ...

This is another arithmetic sequence with a common difference d=2d = 2.

General form: an=2+(n1)2=2na_n = 2 + (n-1) \cdot 2 = 2n

Sum of the first nn terms: Sn=n2(a1+an)=n2(2+2n)=n(n+1)S_n = \frac{n}{2} \cdot (a_1 + a_n) = \frac{n}{2} \cdot (2 + 2n) = n(n + 1)

4. Sequence: -1, 1, -1, 1, -1, 1, ...

This is an alternating sequence with a repeating pattern.

General form: an=(1)n+1a_n = (-1)^{n+1}

Sum of the first nn terms depends on whether nn is odd or even:

  • If nn is even, the sum is 0.
  • If nn is odd, the sum is 1-1.

5. Sequence: 1, 12\frac{1}{2}, 13\frac{1}{3}, 14\frac{1}{4}, 15\frac{1}{5}, ...

This is a harmonic sequence.

General form: an=1na_n = \frac{1}{n}

Sum of the first nn terms is the harmonic sum: Sn=k=1n1kS_n = \sum_{k=1}^{n} \frac{1}{k} This sum does not have a simple closed form like the others.

Recap of Sums

  1. Sn=n(3n1)2S_n = \frac{n(3n - 1)}{2}
  2. Sn=n(n+2)S_n = n(n + 2)
  3. Sn=n(n+1)S_n = n(n + 1)
  4. Sum is 0 if nn is even; 1-1 if nn is odd.
  5. SnS_n is the sum of the harmonic series.

Would you like details on any of these sequences, or help with another topic? Here are some related questions:

  1. How do you derive the formula for the sum of an arithmetic sequence?
  2. Can the sum of an infinite arithmetic sequence be finite?
  3. What is the significance of the harmonic series in mathematics?
  4. How does the alternating sequence affect its sum over time?
  5. Can we approximate the sum of the harmonic series for large nn?

Tip: The sum of an arithmetic sequence can be quickly calculated by multiplying the number of terms by the average of the first and last term.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Arithmetic Sequence
Alternating Sequence
Harmonic Series

Formulas

Arithmetic sequence nth term formula: a_n = a_1 + (n-1) * d
Sum of arithmetic sequence formula: S_n = n/2 * (a_1 + a_n)
Alternating sequence nth term formula: a_n = (-1)^(n+1)
Harmonic series: S_n = sum_{k=1}^{n} (1/k)

Theorems

-

Suitable Grade Level

Advanced High School